2021
DOI: 10.6018/red.438721
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacies in higher education

Abstract: La digitalización de las instituciones de educación superior (IES), debido a la imposibilidad de clases presenciales y tutoría, causada por COVID-19, puso de manifiesto la necesidad de repensar las oportunidades y los obstáculos para el desarrollo de habilidades de los estudiantes. Basado en el marco de alfabetización digital de Martin y Grudziecki (2006), se desarrolló un estudio con el objetivo de identificar las percepciones de los estudiantes con respecto a las habilidades digitales que poseen, los usos y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 14 publications
2
13
0
5
Order By: Relevance
“…Artificial intelligence, automation, information technology and the transfer of tasks from ordinary office spaces to virtual environments are some of the factors that shape the current workplace both inside and outside it [18]. Industry 4.0 is directly related to innovation, creativity and the production of significant digital transformations [19]. The exponential development and the increasingly widespread use of digitalization in all spheres of modern life require the development of advanced digital knowledge and skills necessary for future employment [20].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence, automation, information technology and the transfer of tasks from ordinary office spaces to virtual environments are some of the factors that shape the current workplace both inside and outside it [18]. Industry 4.0 is directly related to innovation, creativity and the production of significant digital transformations [19]. The exponential development and the increasingly widespread use of digitalization in all spheres of modern life require the development of advanced digital knowledge and skills necessary for future employment [20].…”
Section: Introductionmentioning
confidence: 99%
“…This discourages them from attempting to cope. Moreover, age was considered not a significant aspect affecting young people' digital literacy (Monteiro and Leite, 2021). For gender, although statistics report that women are more likely to use smart watches or fitness trackers than men (Chandrasekaran et al, 2020), they have more choices in healthcare services and visit these services (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, academic, industry, and government sources were using advisory bodies to plan educational pathways in education and industry to provide skills and competencies for the digital economy (Gekara et al, 2020). In higher education, problems also emerged; Monteiro and Leite (2021) found that Portuguese universities could not transfer keyboard skills into digital strategies (transformation) for lifelong learning. However, Teixeira et al (2021) established that partnerships in Porto, Portugal, between local government, higher education institutes, and city businesses increased employee digital skills.…”
Section: Skills Talent Resourcesmentioning
confidence: 99%